Sistem Web Pendukung Keputusan Calon Penerima Bantuan Mandi Cuci Kakus di Kabupaten Banyuwangi - Galih Hendra Wibowo; Moh. Nur Shodiq; Desyana Ayu Lestari (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2020)
Village community especially Banyuwangi District is still many who have BWT (Bath Wash Toilet) but do not meet the standard. Such as the absence of buildings in accordance with the quality of construction that meet the needs of society. Waste water and bath rooms are disposed of in residential environments. The Government of the Public Works Department has given attention in addressing this issue through the development assistance of BWT. But in selecting the candidate beneficiaries the election process is still done conventionally. The Decision Support System (DSS) was built to help make it easier to determine the prospective beneficiaries of BWT. There are seven eligibility criteria used to assess prospective beneficiaries. Self-Connection House (CH), monthly dues per family, land contributions, population density level per hectare, individual septic tank ownership, shallow well water quality, kitchen waste water disposal and bathrooms. DSS is processed using Simple Additive Weighting (SAW) method calculation. The SAW method is capable of precise assessment. The calculation of the SAW method is based on the criteria value and the specified preference weight. On the system, there are 8 village data used to test the system process. The highest village Data became the beneficiary village of BWT. Based on the overall level of software quality can be concluded that the level of information system quality in the criteria is very good with a percentage of 94%.